2015
DOI: 10.1016/j.ydbio.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Niche signaling promotes stem cell survival in the Drosophila testis via the JAK–STAT target DIAP1

Abstract: Tissue-specific stem cells are thought to resist environmental insults better than their differentiating progeny, but this resistance varies from one tissue to another, and the underlying mechanisms are not well-understood. Here, we use the Drosophila testis as a model system to study the regulation of cell death within an intact niche. This niche contains sperm-producing germline stem cells (GSCs) and accompanying somatic cyst stem cells (or CySCs). Although many signals are known to promote stem cell self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 94 publications
(133 reference statements)
3
32
0
Order By: Relevance
“…So far, only isolated studies have implicated JAK/STAT in cell survival (Betz et al, 2008;Hasan et al, 2015;Guarner et al, 2014;Ohayon et al, 2009). For example, the apoptosis inhibitor IAP has been suggested to be a positively regulated target of Stat92E, protecting cells from apoptosis (Betz et al, 2008;Hasan et al, 2015). We identify the JAK/STAT effector Zfh2 as a potential repressor of kay and hid activity -a molecular pathway expected to restrain excessive JNK-activity and induction of apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…So far, only isolated studies have implicated JAK/STAT in cell survival (Betz et al, 2008;Hasan et al, 2015;Guarner et al, 2014;Ohayon et al, 2009). For example, the apoptosis inhibitor IAP has been suggested to be a positively regulated target of Stat92E, protecting cells from apoptosis (Betz et al, 2008;Hasan et al, 2015). We identify the JAK/STAT effector Zfh2 as a potential repressor of kay and hid activity -a molecular pathway expected to restrain excessive JNK-activity and induction of apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…However, continuous overexpression of Upd can also induce apoptosis (not shown) and, thus potentially also sustained JNK-dependent compensatory proliferation, driving tissue growth. So far, only isolated studies have implicated JAK/STAT in cell survival (Betz et al, 2008;Hasan et al, 2015;Guarner et al, 2014;Ohayon et al, 2009). For example, the apoptosis inhibitor IAP has been suggested to be a positively regulated target of Stat92E, protecting cells from apoptosis (Betz et al, 2008;Hasan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have attempted complete ablation of ISCs by expressing pro-apoptotic genes, which has proved challenging due to an apparent resistance of some stem cells to apoptosis [5][40][41][42] or embryonic or larval death due to leaky expression of pro-apoptotic factors (data not shown). Our strategy to ablate ISCs/EBs by depleting Hdc supports a model wherein ISCs are largely dispensable for intestinal function and fly survival in non-challenged conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, we detected no lysotracker-positive E(z) mutant GSCs (N=106, Supplementary Figure 2c), indicating increased cell death to be an unlikely cause of their loss. Previous studies have shown that normal GSCs have unique protective mechanisms against cell death [6365]. Loss of E(z) does not seem to abrogate this protection.…”
Section: Resultsmentioning
confidence: 94%